2010
DOI: 10.1080/09540120903373581
|View full text |Cite
|
Sign up to set email alerts
|

The benefit of supplementary feeding for wasted Malawian adults initiating ART

Abstract: Food insecurity is considered to be an important contributor to HIV associated wasting in sub-Saharan Africa. Low body mass index (BMI) is a strong risk factor for early mortality during antiretroviral therapy (ART). Nutritional supplementation has become standard of care in wasted patients starting ART in many countries in the region, but there is no unequivocal evidence base for this intervention. Against this background, we performed a retrospective study to compare food supplementation versus no nutritiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 17 publications
1
56
0
Order By: Relevance
“…Of the nine, seven reported an estimate for the effect of cotrimoxazole on mortality, [28][29][30][31][32][33][34] whereas three reported an estimate for the effect on morbidity. 28,35,36 Two studies also reported the preventive effect on malaria.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the nine, seven reported an estimate for the effect of cotrimoxazole on mortality, [28][29][30][31][32][33][34] whereas three reported an estimate for the effect on morbidity. 28,35,36 Two studies also reported the preventive effect on malaria.…”
Section: Resultsmentioning
confidence: 99%
“…28,35,36 Two studies also reported the preventive effect on malaria. 28,36 Assessment of publication bias indicated that three studies [28][29][30] were of high methodological quality, while the other six [31][32][33][34][35][36] were of moderate methodological quality (Table 4, available at: http://www.who. int/bulletin/volumes/90/2/11-093260).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another randomized supplementary feeding trial in Malawi compared the impact on BMI and fat-free body mass of wasted HIV patients starting ART who were supplemented with specialized, energy dense, ready-to-use, fortified (RUF) spread versus the more commonly used corn-soy blend (CSB) for a short duration of 14 weeks and a historical control group [40,41]. Supplementary feeding with the RUF resulted in a greater increase in BMI and lean body mass than feeding with CSB, but there were no significant observed differences in markers of disease progression, quality of life, or adherence to ART between RUF and CSB groups.…”
Section: Nutrition Supplementation Interventions Targeted To Plhivmentioning
confidence: 99%
“…In two studies the effect of WFP food rations were examined (42,45) . In these studies both study populations were ART naive, which may account for the small-to-modest increases in BMI observed (0·6 and 0·49 kg/m 2 , respectively).…”
Section: Types Of Food Supplementationmentioning
confidence: 99%